Effects of Dietary Protein Levels on Meat Quality, Serum Antioxidant Capacity, and Intestinal Microorganisms in Ningxiang Pigs - Shanghang Liu; Kai Yang; Jie Yin; Jiashun Chen; Qian Jiang; Jing Wang; Bie Tan; Xiaokang Ma; Juan Liu (Antioxidants)
This study aimed to evaluate the impact of five different dietary protein levels on meat quality, serum antioxidant capacity, and intestinal microorganisms of Ningxiang pigs, thus providing new insights into their nutritional needs. One hundred and twenty-five healthy Ningxiang barrows with an average body weight of 53.19 ± 2.12 kg were randomly divided into five groups with five replicates and five pigs per replicate. The diet was formulated using corn, soybean meal, and rice bran meal as raw materials based on net energy. Following the nutritional requirements outlined in the Nutrient Requirements of Swine in China (2020), diets with five different protein levels (crude protein: 11.09%, 12.09%, 13.09%, 14.09%, 15.09%) were formulated. The amino acid levels of lysine, threonine, tryptophan, methionine, valine, isoleucine, and other amino acids were standardized to meet the recommended values, as were other essential amino acids. The experiment lasted for 62 days. The results indicated a linear decrease in the redness and yellowness values of the Longissimus dorsi muscle with increased dietary protein, alongside a quadratic decrease in intramuscular fat (p < 0.01). Notably, muscles from pigs fed with 13.09%, 14.09%, and 15.09% protein diets exhibited significantly lower redness and yellowness than those on a 12.09% protein diet (p < 0.05). Additionally, higher dietary protein levels linearly enhanced the presence of specific fatty acids (C17:0, C17:1, C18:3n3, and C18:3n6) and certain amino acids in the Longissimus dorsi muscle, following a quadratic trend (p < 0.01). The serum GSH-Px content increased linearly with greater dietary protein levels (p < 0.05). Significant variations in cecal and colonic metabolites were observed across different protein levels, affecting the contents of putrescine, cadaverine, spermine, spermidine, and short-chain fatty acids (p < 0.05). Additionally, the increase in dietary protein levels correlates with the growth performance and amino acid profile of the Longissimus dorsi muscle in Ningxiang pigs, presenting a quadratic relationship. Concurrently, the serum antioxidant capacity and cecal bioamine content demonstrate a linear increase. Despite a balanced inclusion of six essential amino acids, both excessively high and low protein levels adversely affect growth and intestinal health. Notably, dietary protein levels of 12.09% and 13.09% yield the optimal growth performance under the specified experimental conditions.